Non-Lethal Concentration of MeHg Causes Marked Responses in the DNA Repair, Integrity, and Replication Pathways in the Exposed Human Salivary Gland Cell Line - Nogueira, Lygia Sega; Vasconcelos, Carolina P.; Plaça, Jessica Rodrigues; Mitre, Geovanni Pereira; Bittencourt, Leonardo Oliveira; Kataoka, Maria Sueli da Silva; de Oliveira, Edivaldo H. C.; Lima, Rafael Rodrigues (Frontiers in Pharmacology, 2021)
In the Brazilian northern Amazon, communities are potentially exposed and vulnerable to methylmercury (MeHg) toxicity through the vast ingestion of fish. In vivo and in vitro studies demonstrated that the salivary glands as a susceptible organ to this potent environmental pollutant, reporting alterations on physiological, biochemical and proteomic parameters. However, it is still unknown the alterations caused by MeHg on gene expression of exposed human salivary gland cells. Therefore, the goal was perform the transcriptome profile of the human salivary gland cell line after exposure to MeHg, using the microarray technique and posterior bioinformatics analysis. The cell exposure was performed using 2.5 µM MeHg. A previously published study demonstrated that this concentration belongs to a range of concentrations that caused biochemical and metabolic alterations in this linage. As a result, the MeHg exposure did not cause lethality in the human salivary gland cells line but was able to alter the expression of 155 genes. Downregulated genes (15) are entirety relating to the cell metabolism impairment, and according to KEGG analysis, they belong to the glycosphingolipid (GSLs) biosynthesis pathway. On the other hand, most of the 140 upregulated genes were related to cell-cycle progression, DNA repair and replication pathway, or cellular defenses through GSH basal metabolism. These genomic changes revealed the effort to the cell to maintain physiological and genomic stability to avoid cell death, being in accordance with the non-lethality in the toxicity test. Lastly, the results support in-depth studies on non-lethal MeHg concentrations for biomarkers identification that interpret transcriptomics data in toxicological tests serving as an early alert of physiological changes in in vitro biological models.